SCIENTIA SACRA IN SUFISM AS WELTANSCHAUUNG CONTEMPORARY MUSLIM SPIRITUALITY - Imron Mustofa (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
This study examines the peripheral area of Sufistic reasoning, where modern humans lose their orientation and cause a psychological crisisâ€”through a fundamental philosophical assessment of theÂ weltanschauungÂ as the axis of Sufism spirituality in Islam, focusing on the contemporary perspective of modern society and the construct ofÂ Scientia sacraÂ as theÂ weltanschauungÂ of contemporary Muslim spirituality. The study results confirm that the fundamental problem that represents the relationship between spirituality and modern society is the dualism of the ontology-epistemic framework, as a result of the split understanding between Sufism and its pseudo. The Sufis have built the concept ofÂ ScientiaÂ sacraÂ based on the integration of theosophical reasoning, ascetic praxis, and philosophical nature. This concept is expected to present conceptual-praxis activities described as exclusiveÂ mujahadahÂ , trendy, and introvertistic that â€œcatharsisâ€ themselves from the worldly bustle but have communal, philosophical valuesÂ closely related to the valuesÂ rahmat al-khalq. The philosophical basis of this movement originated from theosophical reasoning, transformed into praxis asceticism, and developed as philosophical asceticism. These three elements come from the key statement that Sufism is an existential axis for humans, where the crisis of modern humans is the centrifugal motion of that axis. It is what causes the philosophical valuesÂ in Sufistic teachings to experience turmoil, ending in a cathartic process towardsÂ Scientia sacraÂ as the basis of knowledge, metaphysics, and esotericism.